Invasion and dynamics of covert infection strategies in structured insect-pathogen populations - Bonsall, M; Sait, S; Hails, R (2005)
1. Pathogens are known to cause horizontally transmitted overt (fully symptomatic) and vertically transmitted covert (asymptomatic) infections. Here, we explore a range of different covert infection strategies on the persistence and dynamics of insect host-pathogen interactions. 2. The three strategies we explore are (i) sublethal infections in which hosts survive initial infection but suffer costs on fecundity or development, (ii) persistent infections, which are transmitted vertically with minimal costs on fecundity and development and which also confer immunity against superinfection and (iii) persistent infections without immunity against superinfection. 3. We examine the conditions that allow these three strategies to invade. We find that sublethal infections can act to modulate the population dynamics (i.e. cause changes in amplitude and periodicity of cycles) as well as inducing different dynamics (stable and unstable states). This is in line with empirical findings. 4. Covert infection strategies are also able to generate novel dynamics. In particular, over a wide range of parameter space the predicted dynamics of the covert infections without immunity are of a persistent stable interaction solely between the covertly infected hosts and the pathogen, with the exclusion of clean susceptible hosts. 5. Our results suggest that, in general, host-pathogen interactions may be maintained in low-level persistent endemic states without the propensity to show the cyclic oscillations characteristic of enemy-victim interactions. Understanding host-pathogen dynamics requires a knowledge of the factors involved, such as covert infections, that may compensate for the destabilizing effects of time-lags. © 2005 British Ecological Society.